Identifikasi Mikroplastik pada Insang dan Saluran Pencernaan Ikan Nila (Oreochromis niloticus) di Danau Toba Kabupaten Simalungun - Erika Putri Octavani Situmorang; Puji Prastowo; Mufti Sudibyo (Biocaster : Jurnal Kajian Biologi, 2026)
Microplastic pollution in the waters of Lake Toba has the potential to accumulate in aquatic biota, including tilapia (Oreochromis niloticus) cultivated in floating net cages. The presence of microplastics in aquatic organisms is an important concern, because it has the potential to disrupt the balance of aquatic ecosystems and pose a risk to food security for humans. This study aims to identify the shape and color of microplastics in the gills and digestive tract of tilapia, as well as analyze the differences in abundance between the two organs. The research was carried out in June-August 2025 using a quantitative descriptive method. Fish samples were taken from three stations in the waters of Lake Toba, Simalungun Regency, namely tourist areas, boat transportation activities, and residential areas. Microplastic identification was performed visually using a microscope after the degradation of organic matter by the Fenton method. The results showed that the abundance of microplastics in the gill organs was 32 particles/individual, while in the digestive tract as many as 31 particles/individual. The microplastics found are dominated by fibers, fragments, and films with the main colors being green, black, red, brown, and transparent. The results of the independent sample t-test showed a value of p = 0.787 (p > 0.05) which indicated that there was no significant difference in microplastic abundance between the gills and the gastrointestinal tract. These findings confirm that microplastics have been distributed relatively evenly in tilapia organs, so that they have the potential to have an impact on the health of Lake Toba's aquatic ecosystem and food safety from aquaculture fisheries.